The awareness and acceptance of local customers toward Syariah Compliant practices in hotel industry / Nur’hidayah Che Ahmat, Ahmad Hidayat Ahmad Ridzuan and Mohd Salehuddin Mohd Zahari. - Che Ahmat, Nur’hidayah; Ahmad Ridzuan, Ahmad Hidayat; Mohd Zahari, Mohd Salehuddin (2011)
The large growing number of followers of Islam globally and current tourism trends boost up the demand for and supply of Islamic hospitality services. It is believed that the emergence of Islamic financing is one of the driving factors of Syariah Compliant hotels besides the increasing number of Arab and Muslim travellers and their high purchasing power. However, specific guidelines need to be introduced in constructing this concept since there are many different opinions and inconsistencies in understanding such practices among the Syariah scholars and hotel operators. Corpus of past literatures affirmed that currently there is no standardization being introduced and it is worth to mentioned, most of the hotel operators came out with their own interpretation of compliant strategies. They overly concentrated on to be the pioneer while neglecting the main aspect of being a Syariah Compliant hotel. Therefore, this study empirically investigates the awareness and acceptance level of the customers on Syariah Compliant practices. Three areas being tested namely, a) operations, b) interior design, and c) financial. Self-reported questionnaire will be used to gather the data from the customers who have experience staying in the hotel. It is expected that there is a positive relationship between the awareness of the customers on the three criteria tested with their acceptance level. The outcomes of this study will provide the hotel operators with some meaningful insights about the abovementioned issues